ANALYSIS OF REDUCED INORGANIC SULFUR BY DIFFUSION METHODS: IMPROVED APPARATUS AND EVALUATION FOR SULFUR ISOTOPIC STUDIES - Hsieh Y.P.; Shieh Y.N. (My University, 1997)
Separation and determination of reduced inorganic sulfur are important in many ecological and geological studies. Both distillation and diffusion methods can effectively separate acid-volatile sulfide (AVS), chromium(II)-reducible sulfide (CRS), and elemental sulfur (ES) in sediments. The requirement of heating, condensation, and constant attention in the distillation process limits the number of samples that can be processed on a timely basis. The development of the more simple diffusion alternative alleviates the limitation of the distillation method and allows additional samples to be processed. The diffusion method can also separate and determine ES without an extra solvent extraction. The original procedure of the diffusion methods, however, is cumbersome. The original diffusion methods also have not been evaluated for applications in sulfur isotopic studies. We describe in this paper, an improved apparatus and several adjustments to the original procedure which simplify the operation and increase the efficiency of the diffusion method. We also evaluated and confirmed the appropriateness of the diffusion methods for sulfur isotopic analysis.
Keywords: PYRITE; ACID-VOLATILE SULFIDE; CHROMIUM(II)-REDUCIBLE SULFIDE; ELEMENTAL SULFUR